Impact of ESG Performance on Firm Value: A Comparison of Emerging and Developed Markets - Syarkani, Yofi; Subu, Muhammad Arsyad; Waluyo, Imam (Commercium : Journal of Business and Management, 2024)
This study examines the influence of Environmental, Social, and Governance (ESG) performance on firm value, comparing emerging and developed markets, focusing on Indonesia. While ESG’s global impact on firm value is well-documented, research on its effects in Indonesia and similar markets is limited. Developed economies benefit from robust regulatory frameworks and investor demand for ESG integration. In contrast, Indonesia shows an inconsistent ESG-firm value relationship influenced by regulatory progress, investor awareness, and socioeconomic factors. The study aims to: (1) evaluate ESG’s impact on firm value in Indonesia, (2) identify contextual factors mediating this relationship, and (3) determine which ESG dimensions—Environmental, Social, or Governance—most significantly affect valuation. A Structured Literature Review (SLR) of studies from 2020 to 2024 provides insights into ESG impacts in emerging and developed markets, emphasizing Indonesia. Findings reveal that ESG performance generally enhances firm value in Indonesia, with Governance having the most decisive influence. Governance promotes investor confidence and stability, which is highly valued in Indonesia’s market. Social factors, such as community engagement, also contribute to firm value, aligning with Indonesia's emphasis on corporate social responsibility. Environmental factors, however, show limited impact due to low domestic investor prioritization and weak regulatory enforcement. ESG adoption in Indonesia is driven mainly by foreign investors and multinational corporations adhering to global standards. To enhance ESG’s role in firm value, Indonesian regulators should mandate ESG disclosures and incentivize green finance. Firms must focus on governance and social initiatives to build investor confidence.